2009
DOI: 10.1021/jp901747s
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Hydration Force: Water-Mediated Interaction between Two Hydrophilic Plates

Abstract: We performed molecular dynamics simulations on systems containing phosphatidycholine headgroups attached to graphene plates (PC-headgroup plates) immersed in water to study the interaction between phosphatidylcholine bilayers in water. The potential of mean force (PMF) between PC-headgroup plates shows that the interaction is repulsive. We observed three distinct regimes in the PMF depending on the interplate distances: the small distance regime, intermediate distance regime, and large distance regime. We beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
105
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(107 citation statements)
references
References 26 publications
2
105
0
Order By: Relevance
“…These so-called hydration forces arise from the complex interplay of surface group configurational degrees of freedom, desorption of hydration water from polar surface groups, and ordering of the intersurface water film (4). The understanding of hydration forces has recently been advanced by computer simulations that include explicit water molecules (12)(13)(14).In the absence of direct surface-surface interactions, the transition between cavitation-induced attraction and hydration repulsion should coincide with the contact angle characterizing the border between hydrophilic and hydrophobic surface properties; i.e., θ = 90°. In contrast, experiments probing the interactions between similar neutral surfaces with well-defined contact angles demonstrated that even hydrophilic surfaces exhibit short-range attractions not accountable by vdW forces down to typical adhesive contact angles of θ adh = 65°-80°(15-18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These so-called hydration forces arise from the complex interplay of surface group configurational degrees of freedom, desorption of hydration water from polar surface groups, and ordering of the intersurface water film (4). The understanding of hydration forces has recently been advanced by computer simulations that include explicit water molecules (12)(13)(14).In the absence of direct surface-surface interactions, the transition between cavitation-induced attraction and hydration repulsion should coincide with the contact angle characterizing the border between hydrophilic and hydrophobic surface properties; i.e., θ = 90°. In contrast, experiments probing the interactions between similar neutral surfaces with well-defined contact angles demonstrated that even hydrophilic surfaces exhibit short-range attractions not accountable by vdW forces down to typical adhesive contact angles of θ adh = 65°-80°(15-18).…”
mentioning
confidence: 99%
“…These so-called hydration forces arise from the complex interplay of surface group configurational degrees of freedom, desorption of hydration water from polar surface groups, and ordering of the intersurface water film (4). The understanding of hydration forces has recently been advanced by computer simulations that include explicit water molecules (12)(13)(14).…”
mentioning
confidence: 99%
“…Although several theoretical (9)(10)(11) and simulation (12)(13)(14)(15)(16)(17)(18) studies elucidated partial aspects of the HR, none treated the full complexity of the problem and could quantitatively reproduce and explain experimental pressure-distance curves, meaning that the HR mechanism remained essentially unclear. The reason for this is obvious: Theory typically only treats one part of the problem, be it the water-water interactions, the water-surface binding, or the configurational entropy of bilayer molecules, whereas current simulation strategies account for the constant water chemical potential either in the form of a large reservoir (13)(14)(15) or by grand-canonical simulations (16,17). Due to limitations in the numerical accuracy, however, both approaches do not enable quantitative comparison of the HR pressure with experimental data.…”
mentioning
confidence: 99%
“…The main question we address with our simulations in essence is: What is it that keeps the bilayers separated even at high pressures of 10 8 Pa or 1,000 atm? To make progress in this direction, the pressure Π ¼ Π dir þ Π ind is first decomposed into the direct membrane-membrane contribution and all other water-mediated forces, in the following denoted as the indirect contribution (13,17). Note that this decomposition is indepen-dent of the position of the surface through which the pressure is calculated as long as it lies entirely inside the water phase.…”
mentioning
confidence: 99%
“…correlate the measured repulsion force with the properties of a specic physical system. Molecular dynamics (MD) simulations [14][15][16][17][18][19] can help to understand the interbilayer forces on the molecular level.…”
mentioning
confidence: 99%